Peptide 11R-VIVIT stimulates osteoblastogenesis through regulating the expression of nuclear factor of activated T cells cytoplasmic 1 - Li, M.; Wang, X.; Bian, Z.; Yao, W.; He, Q.; Tian, F.; Zhang, J.; Zhu, L. (Cellular and Molecular Biology, 2017)
Osteoporosis is characterized by the imbalance of two relatively independent processes-osteoblastogenesis and osteoclastogenesis. Calcineurin (Cn)/nuclear factor of activated T cells (NFAT)(Cn/NFAT) signaling pathway is involved in these two processes in bone metabolism, but its potential as a target to treat osteoporosis needs to be defined. The aim of this study is to investigate the inhibition of polypeptide 11R-VIVIT onCn/NFAT signaling pathway. Rat calvaria (RC) cells were prepared from experimental model of osteoporosis in rat.11R-VIVIT wasused to treat cultured RC cells from wide type (WT) rat or from osteoporosis (OP) rat, we then measured the expressions of NFATc1, osteopontin (OPN), osteocalcin (OC), cytokines, NFÎºB subunit p65 by real time PCR, western blot or immunofluorescence. Then ALP expression and staining, and alizarin red S (ARS) staining were employed to study the osteoblastodifferentiation. 11R-VIVIT regulates the expression of NFATc1, and some other molecules in Cn/NFAT signaling pathway, such as OPN and OC, at transcriptional level and protein level. Further, it can regulate the expression of inflammatory cytokine like IL-1beta, IL-10 and TNF-alpha and NFÎºB activity. Further, 11R-VIVIT can accelerate osteoblastodifferentiation of RC cells demonstrated by ALP and ARS staining.11R-VIVIT can stimulate the bone formation by decreasing NFATc1 expression and regulating the expression of inflammation related molecules.